An automated, 0.5 Hz nano-foil target positioning system for intense laser plasma experiments. (19th June 2017) - Gao, Ying; Bin, Jianhui; Haffa, Daniel; Kreuzer, Christian; Hartmann, Jens; Speicher, Martin; Lindner, Florian H.; Ostermayr, Tobias M.; Hilz, Peter; Rösch, Thomas F.; Lehrack, Sebastian; Englbrecht, Franz; et al.
Abstract : We report on a target system supporting automated positioning of nano-targets with a precision resolution of $4~\unicode[STIX]{x03BC}\text{m}$ in three dimensions. It relies on a confocal distance sensor and a microscope. The system has been commissioned to position nanometer targets with 1 Hz repetition rate. Integrating our prototype into the table-top ATLAS 300 TW-laser system at the Laboratory for Extreme Photonics in Garching, we demonstrate the operation of a 0.5 Hz laser-driven proton source with a shot-to-shot variation of the maximum energy about 27% for a level of confidence of 0.95. The reason of laser shooting experiments operated at 0.5 Hz rather than 1 Hz is because the synchronization between the nano-foil target positioning system and the laser trigger needs to improve.